AARS2-catalyzed lactylation induces follicle development and premature ovarian insufficiency - Zhi-Ling Zhang; Shu-Ting Ren; Wan-Jie Yang; Xiao-Wen Xu; Shi-Min Zhao; Ke-Fei Fang; Yan Lin; Yi-Yuan Yuan; Xiao-Jin Zhang; Yun-Qin Chen; Wei Xu (Cell Death Discovery)
Abstract Lactate, a metabolite which is elevated in various developmental and pathological processes, exerts its signal through alanyl tRNA synthetases (AARS)-catalyzed protein lactylation. Herein, we report that elevated lactate and gain-of-function mitochondrial AARS (AARS2) mutations-induced hyper-lactylation promotes premature ovarian insufficiency (POI). Serum lactate is elevated in POI patients. POI-driving AARS2 mutations gain lactyltransferase activity. AARS2 lactylates and inactivates carnitine palmitoyl transferase 2 (CPT2), resulting in FFA accumulation that activates peroxisome proliferator-activated receptor γ (PPARγ), and potentiates follicle-stimulating hormone (FSH) to initiate follicle development. These, in synergy with the anabolites accumulation effects of AARS2, promoted lactylation-induced PDHA1 inactivation promote granular cell (GC) proliferation and primordial follicle development. GC-specific AARS2 overexpression does not affect primordial follicle number but speed up follicle depletion. AARS2 ablation or lactylation-inhibiting β-alanine treatments can prevent folliculogenesis and POI traits in mouse. These findings reveal that lactate signal drives follicle development, and inhibiting lactate signal could treat/prevent POI.